FENOMENA JILBAB DIKALANGAN MAHASISWI PRODI STUDI AGAMA-AGAMA FAKULTAS USHULUDDIN DAN STUDI ISLAM UNIVERSITAS ISLAM NEGERI SUMATERA UTARA - Lestari, Nining (Studia Sosia Religia, 2024)
This study discusses "the phenomenon of the hijab among students of the Study Program of Religion, Faculty of Ushuluddin and Islamic Studies, State Islamic University of North Sumatra". The questions answered in this thesis focus on: what is the motivation of female students to use the hijab, what are the implications of the use of the hijab on social behavior. The purpose of this study is to find out how the phenomenon of veiling students in the Study Program of Religion-Religious Studies, Faculty of Ushuluddin and Islamic Studies, State Islamic University of North Sumatra.This type of research is qualitative which is classified as field research with a phenomenological approach that involves observation and interviews with several informants. It is also supported by data obtained from the Study Program of Religions, Faculty of Ushuluddin and Islamic Studies and as supporting literature in this study also uses books, journals or others that are in accordance with the research title.Based on the results of the study, veiled women among students of the 2018 Stambuk Religion Studies Study Program have very diverse educational, family, social and understanding backgrounds. this phenomenon radiates 2 sides, (1) hijabi students who follow modern styles besides wanting to look more fashionable and trendy, they are also comfortable because of the obligation to comply with agency regulations, (2) students who use the syar'i headscarf apart from being an obligation as well as a form of obedience to Allah SWT. and to control behavior by showing the image of Muslim women. some are even veiled with a veil. The social behavior shown by hijab users is very positive, they have ethics and manners in their behavior, both to teaching lecturers and fellow friends, and keep their association from men who are not their mahram.